2012
DOI: 10.1179/002436312803571447
|View full text |Cite
|
Sign up to set email alerts
|

Significant Risks of Oral Contraceptives (OCPs)

Abstract: Pregnancy is not a disease. But more fundamentally, neither is human fertility. They are normal physiologic processes of the sexually mature person. By classifying pregnancy and fertility as disease states, certain entities are able to position contraception as "the cure." Currently, these same organizations want to include oral contraceptive counseling and medications in the new national health-care plan under a preventive care mandate. But it is the physician's role to counsel patients on preventive care mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The incidence of VTE for healthy women can significantly increase with the use of hormonal contraceptives, even women under thirty-five and not-smoking. In a 2012 article about birth control side effects, Dr. Rebecca Peck (Peck and Norris 2012) report that “Oral contraceptives are associated with a three to five times higher risk of VTE” (43). (Van Hylckama et al 2009).…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of VTE for healthy women can significantly increase with the use of hormonal contraceptives, even women under thirty-five and not-smoking. In a 2012 article about birth control side effects, Dr. Rebecca Peck (Peck and Norris 2012) report that “Oral contraceptives are associated with a three to five times higher risk of VTE” (43). (Van Hylckama et al 2009).…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…An effort was made to perform a series of comprehensive literature surveys to better understand immediate and long-term side effects of these agents. Some of these have been previously published (Peck and Norris 2012; Williams 2017; Keenan et al 2018; Williams et al 2018), while others are included here for the first time. Comparison of the scientific literature with the current prescribing information revealed that many of these risks, although well documented in the peer-reviewed literature, are not included in the prescribing information.…”
mentioning
confidence: 99%
“…4,5 However, COCs have also caused various side effects such as depression, migraine headaches, breast and cervical cancer, stroke, cardiovascular diseases, venous thromboembolism and high systolic blood pressure, inflammatory bowel disease, benign or malignant liver tumors, and obesity. [6][7][8][9][10][11][12] The liver is one of the main secretory organs that play a fundamental role in carbohydrate, protein, and lipid metabolism. Liver hepatocyte cells are rich in the endoplasmic reticulum (ER).…”
Section: Introductionmentioning
confidence: 99%